Philosophy of light: an alternative perspective on Zhang Zai’s “Qi-based learning” - Tengfei Li (Trans/Form/Ação)
Zhang Zai’s “qi-based learning” contains extensive discussions on the concept of brightness (ming 明). By incorporating the core insights from the German translation of Zhengmeng (正蒙), this paper emphasizes the crucial role of light in understanding Zhang Zai’s thought and aims to interpret it as a philosophy of light. From an epistemological standpoint, Zhang Zai links qi closely with light, framing his philosophy as a doctrine of manifestation. Brightness, in this context, is not limited to visibility, but also encompasses the invisible xiang 象, which manifests through the light of shen 神. Zhang Zai metaphorically conceptualizes shen as a unity of giving and receiving light. In this framework, the generative act of shen is understood as the productive stimulation (gan 感) emerging from the undifferentiated foundation. Ultimately, this philosophy of light points to the spiritual realm of “right lightening” (zhenming 貞明), which refers to the penetrating perspicacity of Confucian sages who fully perceive the brightness.